Dental eruption patterns and their relationship to systemic health conditions in children - Ahmed, Neveen M.; Alzahrani, Nada S.; Asali, Afnan S.; Khormi, Nouh H.; Abulsaud, Hajar A.; Alqahtani, Saad A.; Alshehri, Nawaf A.; Almansour, Sara H.; Al-Zahrani, Raghad A.; Alshalawi, Rayan F.; Alrashidi, Albandari G. (International Journal Of Community Medicine And Public Health, 2025)
Dental eruption patterns serve as vital indicators of pediatric health, reflecting a complex interplay between genetic, systemic, environmental, and nutritional factors. These patterns provide insights into a child’s overall health and development, often revealing early signs of systemic conditions or developmental abnormalities. Hormonal imbalances, such as those caused by hypothyroidism or hyperthyroidism, are known to affect the timing and sequence of tooth eruption. Delays in eruption can also result from chronic systemic diseases like diabetes mellitus or kidney disease, as disruptions in metabolic processes impact bone and dental development. Nutritional deficiencies, particularly in calcium, phosphorus, and vitamin D, play a critical role in influencing eruption. Malnutrition often leads to delayed eruption and enamel hypoplasia, with such dental anomalies frequently accompanying stunted growth and systemic deficiencies. Genetic syndromes like Down syndrome and cleidocranial dysplasia further highlight the link between eruption patterns and systemic health, with distinct dental features such as delayed eruption and supernumerary teeth reflecting underlying genetic mutations. Environmental exposures, including high fluoride levels or lead toxicity, have been shown to disrupt dental development, leading to structural anomalies and altered eruption timelines. Additionally, psychological and behavioral factors, such as chronic stress, may interfere with normal eruption by affecting hormonal and metabolic pathways. Dental eruption assessments thus provide a non-invasive, accessible tool for identifying systemic and developmental conditions in children. Incorporating these evaluations into routine pediatric healthcare can enhance diagnostic accuracy and support early intervention for a wide range of health concerns. Understanding the multifaceted influences on eruption patterns enables clinicians to adopt a more holistic approach to pediatric care, fostering better outcomes for both oral and overall health.